Incidence of Postreperfusion Hyperfibrinolysis in Liver Transplantation by Donor Type and Observed Treatment Strategies. (2nd December 2022) - Krom, Russell J.; Welsby, Ian J.; Fuller, Matthew; Barbas, Andrew S.; Gao, Qimeng; Anwar, Imran J.; Dunkman, W. Jonathan
Abstract : BACKGROUND: Hyperfibrinolysis is a possible complication during liver transplantation, particularly immediately after reperfusion. METHODS: We performed a retrospective study to examine the incidence, treatment, and resolution of postreperfusion hyperfibrinolysis in patients undergoing liver transplantation at Duke University Hospital from 2015 to 2020. RESULTS: Out of 535 patients undergoing liver transplantation, 21 or 3.9%, 95% CI (2.5–5.9), had hyperfibrinolysis after reperfusion. Hyperfibrinolysis occurred in 16 of 511 (3.1%) patients receiving livers from DBD donors, 5 of 18 (27.8%) patients receiving livers from donation after circulatory death (DCD) donors, and 0 of 6 (0.0%) patients receiving livers from living donors. Fibrinolysis was treated with cryoprecipitate (12/21), a combination of cryoprecipitate and tranexamic acid (3/21), or neither (6/21) and resolved within several hours in all cases. CONCLUSIONS: Anesthesiologists should be aware of the possibility of postreperfusion hyperfibrinolysis in liver transplantation, particularly with DCD donors, and may consider treatment with cryoprecipitate or tranexamic acid. Further work is needed to identify any potential differences, such as faster resolution of fibrinolysis, between different treatment modalities.